Legal Review of Siri's Marriage Based on Law Number 1 of 1974 Concerning Marriage - Yossi Aries Prasetya; M. Hidayat; Handyka PrayogiLesmana (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
Marriage is a living together of a man and a woman who fulfill the conditions included in the regulation. The purpose of the research is to describe and identify the legal review of siri marriage and to know and analyze the legal consequences of siri marriage according to Law Number 1 1974 concerning Marriage. The research method uses the legal sociological juridical method, which means a research approach that studies the influence of society on law. The results of this research are unregistered marriages or marriages between a man and a woman that are not announced and without the presence of wedding witnesses, carried out without being registered with the marriage registrar with the aim that the general public will not know about them. The legal consequences of the perpetrators of unregistered marriages, That legally, unregistered marriages are invalid if there is no legal record, as explained in Law Number 1 of 1974 as amended by Law Number 16 of 2019 concerning Marriage. Unregistered marriages have many negative impacts on women (wives) and children.